The Effect of Asset Structure, Asset Growth, and Sales Growth on The Capital Structure - Padillah, Nur; Sebayang, Minda Muliana Br.; Ramadhani, Sari Nuzullina (University of Muhammadiyah Malang, 2024)
The optimal capital structure is the balance of debt and equity by maximizing the company’s value through prudent investment efforts and improving the financial and operational performance of each business organization or company. This study aims to analyze the effect of asset structure, asset growth, and sales growth on the capital structure of consumer goods companies listed on the Indonesia Stock Exchange in 2018-2022. The population in this study includes 46 consumer goods companies listed on the Indonesian Stock Exchange in 2018-2022. The sample used after purposive sampling was 23 companies. Analysis methods used in this study using multiple linear regression with IBM SPSS Statistics version 26 software. The data analysis results show that asset structure and sales growth positively and significantly affect capital structure. In contrast, asset growth has a negative and insignificant effect on capital structure. The company must leverage these factors to improve its capital structure.